Pengaruh Kurangnya Literasi serta Kemampuan dalam Berpikir Kritis yang Masih Rendah dalam Pendidikan di Indonesia (Current Research in Education: Conference Series Journal, 2022)
Lack of literacy and low critical thinking skills are among the obstacles that occur in education in Indonesia. This is based on the facts of some students who still have low reading interest and cannot think critically in obtaining reliable and accountable information. Therefore, it takes several efforts to increase reading interest in children and the ability to think critically for each individual in the hope of creating golden generations that are able to compete globally. So that this paper is motivated by the steps that are being made in educational literacy in Indonesia, the impact of the low literacy culture, the low literacy ranking in Indonesia when compared to other countries, and the low critical thinking skills in education.